FAKTOR LINGKUNGAN YANG MELATAR BELAKANGI KONSUMSI MINUM-MINUMAN KERAS PADA REMAJA DI DESA GAYAMAN KECAMATAN MOJOANYAR - MOJOKERTO - HADI KUSUMA, YUDHA LAGA (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2016)
Adolescence is a time where a lot of people suffer from anxiety, restlessness, and confusion when searching an identity. At this time some of the teenagers who thought with consuming drinking may increase their confidence becomes more and more acceptable to the environment or peers. Many factors can influence drinking behavior in adolescents, because the purpose of this study was to determine the environmental background of consumption drinking in adolescents in Gayaman Village, District Mojoanyar - Mojokerto. This study used analytical method and crossectional approach. The population in this study were all teenagers at Gayaman Mojoanyar Mojokerto. The sampling technique used was accidental sampling so that the sample was 42 adolescents. Data analized by using regression analysis (5 predictors). The results showed a positive correlation between environmental factors such as family aspect (rX1Y = 0.622 and p = 0.000 and p <0.001) and aspects of school friends (rX3Y = 0.622 and p = 0.000 and p <0.001) with the consumption of drinking on teens. This study showed that the importance of the role of family harmony, the application of norms in the family and the character of a teenage school friends in determining the behavior of drinking that occurs in adolescents.Key words : environment, drink, consumme, teen